The role of bacterial diversity on the antibiotic and herbicide biodegradation in agricultural soils - Souza, Adijailton José de (2021)
Soil microbiome is essential for providing ecosystem services. The relationship between microbial diversity and ecosystem services is well elucidated for soil microbiome collective functions (i.e. organic matter decomposition and carbon assimilation). However, this relationship remains poorly understood for more specific functions (pesticides and o other xenobiotics degradation). Here, the dilution-to-extinction approach, radiorespirometry and high-throughput sequencing of 16S rRNA gene were used to assess the role of bacterial diversity depletion in the dissipation of antibiotic sulfadiazine (SDZ) and herbicide atrazine (ATZ), which are widely used in pig farming and agriculture, respectively. SDZ microcosm was assembled using paralel soils without (S1) and with (S2) a long-term of swine manure application. While the ATZ microcosm was assembled using Pasture Soil (GS, without long- term of ATZ application) and Cultivated Soil (CS, with long-term of ATZ application). Swine manure application promoted increases in pH and organic carbon and macronutrient contents, as well as impacted the soil bacterial community structure and diversity. The bacterial diversity depletion reduced SDZ mineralization (14C-CO2) and non-extractable residue (NER) formation, but NER recovered after 42 d of incubation. Surprisingly, the non-manured soil ( treatment NS- S1) had a faster SDZ dissipation rate (DT90 = 2.0 versus 21 d) and had a large number of bacterial families involved in the main SDZ dissipation pathways (14C-CO2 and mainly NER), such as Isosphaeraceae, Ktedonobacteraceae, Acidobacteriaceae_Subgroup_1, Micromonosporaceae and Sphingobacteriaceae. Similarly, land use and the long-term of atrazine application promoted changes in the soil physico-chemical attributes, bacterial community structure, diversity and composition, as well as in its capacity to dissipate atrazine. Proteobacteria, Bacteroidetes, Firmicutes, Actinobacteria, Acidobacteria, Verrucomicrobia, Planctomycetes and Gemmatimonadetes were the dominant phyla in both soils (GS and CS). Atrazine minerazation was reduced by 12-fold when compared to the worst scenarios of bacterial diversity depletion. Long-term atrazine application resulted in greater bacterial community efficiency in herbicide dissipation. Bacterial diversity depletion reflected in the reduction of complexity, classification of species (specialists, generalists and very rare), in addition to increases in the abundance of functions related to obtaining energy and nitrogen transformations. Twelve bacterial genera (Ralstonia, Nitrospira, Hirschia, MND1, Candidatus_Koribacter, OM27_clade, Arenimonas, Occallatibacter, Bryobacter, UTBCD1, Ellin6067 and Crenobacter) correlated with atrazine mineralization, suggesting the selection of these genera as potential atrazine degraders. The NER formation was the SDZ primary dissipation route and had the greatest impact of the bacterial diversity depletion. While mineralization was the ATZ primary dissipation route in cultivated soil (CS). The bacterial diversity depletion resulted in simplified bacterial communities, greater imbalance in the niches occupation, as well as higher abundance of functions associated with obtaining energy.